Do floral and ecogeographic isolation allow the co‐occurrence of two ecotypes of Anacamptis papilionacea (Orchidaceae)?. Issue 15 (2nd July 2021) - Cozzolino, Salvatore; Scopece, Giovanni; Lussu, Michele; Cortis, Pierluigi; Schiestl, Florian P.
Abstract: Ecotypes are relatively frequent in flowering plants and considered central in ecological speciation as local adaptation can promote the insurgence of reproductive isolation. Without geographic isolation, gene flow usually homogenizes the allopatrically generated phenotypic and ecological divergences, unless other forms of reproductive isolation keep them separated. Here, we investigated two orchid ecotypes with marked phenotypic floral divergence that coexist in contact zones. We found that the two ecotypes show different ecological habitat preferences with one being more climatically restricted than the other. The ecotypes remain clearly morphologically differentiated both in allopatry and in sympatry and differed in diverse floral traits. Despite only slightly different flowering times, the two ecotypes achieved floral isolation thanks to different pollination strategies. We found that both ecotypes attract a wide range of insects, but the ratio of male/female attracted by the two ecotypes was significantly different, with one ecotype mainly attracts male pollinators, while the other mainly attracts female pollinators. As a potential consequence, the two ecotypes show different pollen transfer efficiency. Experimental plots with pollen staining showed a higher proportion of intra‐ than interecotype movements confirming floral isolation between ecotypes in sympatry while crossing experiments excluded evident postmating barriers. Even if not completely halting the interecotypes pollen flow in sympatry, such incipient switch in pollination strategy between ecotypes may represent a first step on the path toward evolution of sexual mimicry in Orchidinae. Abstract : Without geographic isolation, gene flow usually homogenizes the allopatrically generated phenotypic and ecological divergences, unless other forms of reproductive isolation keep them separated. Here, we investigated two orchid ecotypes with marked phenotypic floral divergence that coexist in contact zones. We found that the two ecotypes show different ecological habitat preferences with one being more climatically restricted than the other. The ecotypes remain clearly morphologically differentiated both in allopatry and in sympatry and differed in diverse floral traits. Despite only slightly different flowering times, the two ecotypes achieved floral isolation thanks to different pollination strategies.